Die Auswirkungen von Wirtschaftskrise und Wirtschaftsreformen auf das Wanderungsverhalten in Kuba - Bähr, Jürgen; Mertins, Günter (ERDKUNDE, 1999)
The study investigates to what extend the migration patterns in Cuba have been changed through the economic crisis and subsequent early economic reforms. Therefore, predominantly the official statistics are evaluated; they are considered relatively reliable, for each change of residence is officially registered which is the precondition for the state allotment of goods of the basic needs of ‘libreta’. Along with that, first results of a nation-wide poll concerning migration movement, which was carried out in 1995, as well as our own collected data and observations, are taken into account. Hereafter, the central question is to be answered in a differentiated way. On the one hand, previous migration tendencies, as the emigration to the USA, the inmigration into the capital and the out-migration from the peripheral eastern part of the country, have noticeably increased. On the other hand, however, new migration destinations have developed. Those are not only the considerably extended or newly founded tourism centres, but also favourably situated agrarian areas (‘Gunsträume’) which have on the one hand hugely profited from the reform in the agrarian regions, and on the other hand have cushioned a part of the employees dismissed from state industrial firms and service enterprises. The partial liberalisation of the labour market by the admission of Work on one‘s own account has allowed labour-orientated migrations come to the fore. These are likely to increase in the future and will on the whole lead to an intensified attractiveness of the bigger cities. With that, the regional disparities, which could have been to a large extend removed during the socialist era, will increase again.